Pandemic Influenza A(H1N1) in Cote d'Ivoire: health-care providers’ knowledge of influenza and attitudes towards vaccination - Coulibaly, Daouda; Nzussouo, Ndahwouh T; Kadjo, Hervé A; Traoré, Youssouf; Ekra, Daniel K; Chérif, Djibril; Kouassi, Paquin D; N’gattia, Anderson K; Dagnan, Simplice N (The Journal of Infection in Developing Countries, 2013)
Introduction: During the 2009 influenza A(H1N1) pandemic (pH1N1), different methods were promoted to reduce the spread of influenza, including respiratory etiquette and vaccination. To identify knowledge gaps about influenza and to plan the vaccination campaign against the pandemic in Côte d’Ivoire, a survey was conducted among health-care providers (HCPs) to assess their knowledge about influenza and their willingness to be vaccinated. Methodology: A cross-sectional survey was performed in the city of Abidjan on 16-18 February 2010, in the three university teaching hospitals, a randomly selected general hospital, and two randomly selected private clinics. In face-to-face interviews, 383 health-care professionals were asked questions about their knowledge of influenza, means of influenza prevention, and their willingness to be vaccinated. Data analysis, both univariate and multivariate, was performed using SPSS. Results: Willingness to be vaccinated against pH1N1 was 80% (n = 284), and 83% of the HCPs would recommend the vaccine to others. The respiratory mode of transmission of influenza was known by 85% (n = 295) of the participants and 50% (n = 174) believed that seasonal influenza virus and pH1N1 virus were different. In a multivariate model, the factors significantly associated with willingness to receive pH1N1vaccine were fear of pH1N1 disease (OR = 2.1; IC = 1.02-4.35), having only a high school education (OR = 8.28; IC = 2.04-33.60), and feeling at risk to contract pH1N1 (OR = 11.43; IC = 4.77-27.38). Conclusion: The willingness to be vaccinated against influenza A (H1N1) by health professionals is real.